2021
DOI: 10.1055/s-0040-1721315
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Strength of an Indirect Composite Modified with Single-Wall Carbon Nanotubes

Abstract: Objectives The low resistance to fracture has limited the use of indirect composite resins for dental restorations, particularly in regions that are exposed to strong occlusal forces. To overcome this issue, different types of reinforcement for composites have been proposed, one of which is carbon nanotubes (CNTs). The aim of this study was to evaluate the flexural resistance of one commercial indirect composite resin (Sinfony, 3M/ESPE) after incorporation of single-wall carbon nanotubes (SWCNTs; Sigma–Aldrich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…A study conducted by Pennisi et al however, revealed that the incorporation of SWCNTs in the polymer composite did not improve the bending strength of indirect composite resin [65]. In contrast, the flexural strength was improved when SWCNTs were modified with SiO2 and functionalized with allytriethoxysilane (ATES) before being incorporated into composite resins [65]. On the other hand, Borges et Glass ionomer cements (GICs) are an example of dental restorative materials that have interesting characteristics for the application as dental luting materials [58] due to their fascinating properties such as biocompatibility, good thermal insulation at oral temperature, good antibacterial activity and fluoride release [67].…”
Section: Applications Of Cnts In Dentistrymentioning
confidence: 92%
See 1 more Smart Citation
“…A study conducted by Pennisi et al however, revealed that the incorporation of SWCNTs in the polymer composite did not improve the bending strength of indirect composite resin [65]. In contrast, the flexural strength was improved when SWCNTs were modified with SiO2 and functionalized with allytriethoxysilane (ATES) before being incorporated into composite resins [65]. On the other hand, Borges et Glass ionomer cements (GICs) are an example of dental restorative materials that have interesting characteristics for the application as dental luting materials [58] due to their fascinating properties such as biocompatibility, good thermal insulation at oral temperature, good antibacterial activity and fluoride release [67].…”
Section: Applications Of Cnts In Dentistrymentioning
confidence: 92%
“…As such, the CNTs have been proposed to be a promising candidate to be modified with the laboratory-processed composite resin [64] in order to enhance their flexural resistance. A study conducted by Pennisi et al however, revealed that the incorporation of SWCNTs in the polymer composite did not improve the bending strength of indirect composite resin [65]. In contrast, the flexural strength was improved when SWCNTs were modified with SiO2 and functionalized with allytriethoxysilane (ATES) before being incorporated into composite resins [65].…”
Section: Applications Of Cnts In Dentistrymentioning
confidence: 98%